Comparison of a New Triazole Antifungal Agent, Schering 56592, with Itraconazole and Amphotericin B for Treatment of Histoplasmosis in Immunocompetent Mice - Connolly, Patricia (American Society for Microbiology, 1999)
A murine model of intratracheally induced histoplasmosis was used to evaluate a new triazole antifungal agent, Schering (SCH) 56592, for treatment of histoplasmosis. MICs were determined for SCH 56592, amphotericin B, and itraconazole by testing yeast-phase isolates from 20 patients by a macrobroth dilution method. The MICs at which 90% of the isolates are inhibited were for 0.019 μg/ml for SCH 56592, 0.5 μg/ml for amphotericin B, and ≤0.019 μg/ml for itraconazole. Survival studies were done on groups of 10 B6C3F(1) mice with a lethal inoculum of 10(5). All mice receiving 5, 1, or 0.25 mg of SCH 56592 per kg of body weight per day, 2.5 mg of amphotericin B per kg every other day (qod), or 75 mg of itraconazole per kg per day survived to day 29. Only 44% of mice receiving 5 mg of itraconazole/kg/day survived to day 29. Fungal burden studies done in similar groups of mice with a sublethal inoculum of 10(4) showed a reduction in CFUs and Histoplasma antigen levels in lung and spleen tissue in animals treated with 2 mg of amphotericin B/kg qod, 1 mg of SCH 56592/kg/day, and 75 mg of itraconazole/kg/day, but not in those treated with lower doses of the study drugs (0.2 mg of amphotericin B/kg qod, 0.1 mg of SCH 56592/kg/day, or 10 mg of itraconazole/kg/day). Serum drug concentrations were measured 3 and 24 h after the last dose in mice (groups of five to seven mice), each treated for 7 days with SCH 56592 (10 and 1 mg/kg/day) and itraconazole (75 and 10 mg/kg/day). Mean levels measured by bioassay were as follows: SCH 56592, 10 mg/kg/day (2.15 μg/ml at 3 h and 0.35 μg/ml at 24 h); SCH 56592, 1 mg/kg/day (0.54 μg/ml at 3 h and none detected at 24 h); itraconazole, 75 mg/kg/day (22.53 μg/ml at 3 h and none detected at 24 h); itraconazole, 10 mg/kg/day (1.33 μg/ml at 3 h and none detected at 24 h). Confirmatory results were obtained by high-pressure liquid chromatography assay. These studies show SCH 56592 to be a promising candidate for studies of treatment of histoplasmosis in humans.